Obesidade e maturação sexual precoce em escolares de Florianópolis - SC - Adami, Fernando [UNESP]; Vasconcelos, Francisco De Assis Guedes De (Associação Brasileira de Saúde Coletiva, 2008)
OBJECTIVE: To investigate the relationship between early sexual maturation and obesity among students aged 10-14 years from the city of Florianopolis. METHODS: A total of 629 students (277 males and 352 females) aged 10-14 years were included in the study. The sample was obtained from two private schools and two public schools in the city of Florianopolis. The body mass index (BMI) was used for determining overweight and obesity. The values of weight, height, and BMI Z score according to gender and age were determined. The LMS method was utilized to determine Z score values. Sexual maturation was evaluated by Tanner stages for both males and females. Subjects were grouped using age-adjusted tertiles for each Tanner stage and gender. Subjects in the first tertile were considered early maturing, while subjects in the second tertile were considered the reference group. RESULTS: Early maturing girls were heavier (²=-0.21, p<0.05), taller (²=-0.15, p<0.05) and had higher BMI values for age (²=-0.3, p<0.05) than girls of other groups. Early maturing boys were taller for age (²=-0.21, p<0.05) than boys of other groups. The prevalence of overweight including obesity of early maturing girls was higher than for the reference group (p=0.01). No association was found between overweight, including obesity, and early sexual maturation among boys (p=0.648). CONCLUSIONS: The results of this study are similar to other studies that declare that early maturing girls present a higher prevalence of obesity than non-early maturing girls. The present study did not show any association for boys regarding early sexual maturation and obesity.

OBJETIVOS: Investigar a associação entre maturação sexual precoce e obesidade em meninos e meninas de 10 a 14 anos de Florianópolis. MÉTODOS: Participaram do estudo 629 escolares entre 10 e 14 anos (277 meninos e 352 meninas), obtidos de duas escolas públicas e duas escolas privadas da região central do município. Foi utilizado o índice de massa corporal (IMC) para determinação de sobrepeso e obesidade. Os valores de Z escore para IMC, peso e estatura foram determinados de acordo com sexo e idade. Para obtenção dos valores de Z escore, utilizou-se o método LMS. A maturação sexual foi avaliada de acordo com planilha contendo 5 estágios de maturação sexual para cada sexo. Os indivíduos foram agrupados por tercis da idade de acordo com estágio e sexo. O 1º tercil foi considerado como maturação sexual precoce; e o 2º tercil, como grupo de referência. RESULTADOS: As meninas com maturação sexual precoce têm maiores valores de Z escore Peso (²=-0,21, p<0,05), Z escore estatura (²=-0,15, p<0,05) e Z escore IMC (²=-0,3, p<0,05) do que as meninas dos outros grupos. Já os meninos com maturação sexual precoce apresentam maiores valores de Z escore estatura (²=-0,21, p<0,05). As meninas com maturação sexual precoce têm duas vezes mais chances de ter sobrepeso, incluindo obesidade, do que meninas do grupo de referência, com associação significante (p=0,01) Nos meninos, não foi encontrada associação significante (p=0,648). CONCLUSÃO: Os achados deste estudo corroboram aqueles da literatura que afirmam que meninas com maturação sexual precoce têm maiores prevalências de sobrepeso, incluindo obesidade, do que as meninas do grupo de referência. Em relação aos meninos, o presente estudo não encontrou associação entre maturação sexual precoce e obesidade.
Obesity and early sexual maturation among students from Florianopolis - SC
Keywords: Obesity; Sexual Maturation; Students; Adolescents; Obesidade; Maturação sexual; Escolares; Adolescentes